Hyperuricemia and Microalbuminuria are Independently Associated with Hypertension - Pramanik, Md. Safayet Hossain; Ahmed, Md. Abu Saleh; Hossain, Md. Saeed; Hakim, Md. Abdul; Aziz, Md. Tamim; Islam, Md. Shoriful (Cardiology and Cardiovascular Medicine, 2024)
Background: High uric acid (UA) levels have been traditionally considered a risk factor for gouty arthritis and kidney stones. However, it has emerged recently that elevated serum UA level is a risk factor for hypertension, chronic kidney disease, and coronary artery disease. Microalbuminuria is associated with an increased risk of hypertension, renal impairment, and cardiovascular morbidity. Evidence suggests untreated essential hypertension increases serum uric acid and urinary albumin excretion. Aim of the study: The study aims to observe the association of serum uric acid level and microalbuminuria with hypertension. Methods: This cross-sectional study was conducted at the Nephrology Department of Dhaka Medical College & Hospital, Dhaka, from March 2021 to August 2022 over 18 months. One hundred sixteen male and female patients were included in this study; all were dipstick-negative for proteinuria. Among them 58 patients with essential hypertension, and the remaining 58 were normotensive subjects (according to JNC VIII). After approval from the Research Review Committee (RRC) of Nephrology and Ethical Review Committee (ERC) of DMC, written informed consent was obtained from all study subjects. Patient’s data on baseline characteristics (age, gender, blood pressure) and complete clinical and laboratory data were recorded in a predesigned data collection sheet. The uricase method measured serum uric acid, and microalbuminuria was calculated using the immune-turbidimetric method. After data collection, data analysis was done with SPSS version 26. Result: It was observed that more than one-third (37.9%) of patients belonging to age were 41-50 years in the hypertensive group and 44.8% in the normotensive group. The mean age was 44.79±9.13 years in hypertensive and 41.07±9.87 years in normotensive. Almost two-thirds (65.5%) of patients were male in the hypertensive group and 33(56.9%) in the normotensive group. The two groups' age differences were statistically significant (p<0.05). In male patients, it was observed that more than onethird (34.2%) of patients had hyperuricemia in hypertensive, which was significantly (p<0.05) associated between the two groups. Hyperuricemia had a 5.2 times risk of developing hypertension (OR=5.2; 95% CI=1.18- 26.11). In female patients, it was observed that three (15.0%) patients had hyperuricemia in hypertensive and 1(4.0%) in normotensive, which was not significantly (p>0.05) associated between the two groups. The mean of S. Uric acid was 5.3±1.3 in patients with stage I hypertension and 6.4±1.2 in patients with stage II hypertension. The differences in S. Uric acid were statistically significant (p<0.05) between stage I and II hypertension. Almost two-thirds (60.3%) of patients had microalbuminuria in the hypertensive group, which was statistically significant (p<0.05) between the two groups. Microalbuminuria had 16.13 times the risk of developing hypertension (OR=16.13; 95%CI=5.15-54.08). The differences in microalbuminuria were statistically significant (p<0.05) between the two stages of hypertension. Conclusion: This study demonstrates a significant solid association between uric acid level and microalbuminuria with hypertension. There was an association between serum uric acid and microalbuminuria in hypertensive patients with systolic diastolic blood pressure and MAP. There was also a significant association between S. uric acid and microalbuminuria in hypertensive patients.